2022
DOI: 10.51894/001c.30766
|View full text |Cite
|
Sign up to set email alerts
|

“Fantasy Points” associated with Professional Athlete Performance after Lumbar Discectomy or Microdiscectomy

Abstract: The treatment of Lumbar Disc Herniation (LDH) in elite athletes is a debated topic that lacks consensus in the literature due to varying outcome reporting methods. The objective of this study was to quantify the overall performance of a sample of professional athletes before and after receiving a lumbar discectomy or microdiscectomy in a cohort of players in the National Football League (NFL), National Basketball Association (NBA), National Hockey League (NHL) and Major League Baseball (MLB). METHODSThe author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Scientists & sport physicians reported that effective treatment of LDH and successful return to sports in elite athletes is a debated actual topic that lacks consensus in the scientific literature [39]. Also, investigators reported that state of the evidence suggests that there are deficits in identifying the optimal prevention and rehabilitation prescription components for the variety of LBP-inducing injuries in athletic population [6].…”
Section: Discussionmentioning
confidence: 99%
“…Scientists & sport physicians reported that effective treatment of LDH and successful return to sports in elite athletes is a debated actual topic that lacks consensus in the scientific literature [39]. Also, investigators reported that state of the evidence suggests that there are deficits in identifying the optimal prevention and rehabilitation prescription components for the variety of LBP-inducing injuries in athletic population [6].…”
Section: Discussionmentioning
confidence: 99%
“…MLB player information was collected from FanGraphs ( http://www.fangraphs.com ). This was in accordance with a previously established methodology [ 13 ].…”
Section: Methodsmentioning
confidence: 98%
“…Next, the fantasy points in the NHL [13] are calculated using formulas based on a player's position. Specifically, the formula for defensemen is: Moreover, the fantasy points for NBA players are not calculated using standard points but are based on the league.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations